2009
DOI: 10.1080/10428190802709453
|View full text |Cite
|
Sign up to set email alerts
|

The role of soluble and cell-surface expressed 4-1BB ligand in patients with malignant hemopoietic disorders

Abstract: The TNFR family member 4-1BB and its ligand 4-1BBL are involved in the costimulation of T-cells and tumor-derived soluble (s)4-1BBL may influence the interaction of malignant cells with the immune system. Here, we report that cell-surface-expressed (c)4-1BBL can be expressed on mononuclear blood cells from patients with acute myeloid leukemia (AML) (n = 35), myelodysplasia (n = 5) or non-Hodgkin lymphoma (n = 11) and can be coexpressed on varying proportions of lymphoid or myeloid malignant cells and on dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…In previous studies, we revealed that the release of so4-1BBL from AML-blast samples leads to a higher plasma level and expression correlated with prognostically adverse AML subtypes what might be explained by a binding of so4-1BBL to T-cells, thereby inhibiting T-cell-c4-1BB binding to tumor cells. Moreover, c4-1BBL is known to be expressed on AML blasts’ surface8 and was stated to have an impact in the blasts’ maturation processes due to its reverse signaling capability when stimulated as shown in 15 of 21 not closer specified AML samples in a study of Cheng et al 30 that could not be confirmed in our study, probably due to a different composition of our pt cohort. In cut-off analyses, we correlated significantly higher 4-1BBL expression with shorter (but not significant) DFS and OS times, thereby providing evidence of correlation not only of a higher so4-1BBL release but also of a higher c4-1BBL expression in the case of unfavorable prognosis.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In previous studies, we revealed that the release of so4-1BBL from AML-blast samples leads to a higher plasma level and expression correlated with prognostically adverse AML subtypes what might be explained by a binding of so4-1BBL to T-cells, thereby inhibiting T-cell-c4-1BB binding to tumor cells. Moreover, c4-1BBL is known to be expressed on AML blasts’ surface8 and was stated to have an impact in the blasts’ maturation processes due to its reverse signaling capability when stimulated as shown in 15 of 21 not closer specified AML samples in a study of Cheng et al 30 that could not be confirmed in our study, probably due to a different composition of our pt cohort. In cut-off analyses, we correlated significantly higher 4-1BBL expression with shorter (but not significant) DFS and OS times, thereby providing evidence of correlation not only of a higher so4-1BBL release but also of a higher c4-1BBL expression in the case of unfavorable prognosis.…”
Section: Discussioncontrasting
confidence: 64%
“…4-1BBL is also known to mediate important functions of apoptosis and regulates development of solid tumor (seen in colon carcinoma cell lines HT-29, Colo205, and HCT116), as well as AML in cases of coexpression 7 8. Membrane-bound (c) 4-1BBL was previously reported to be expressed on AML blasts 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AML blasts often weakly express co‐stimulatory molecules which may favour their escape from T cell‐mediated killing, and the probability of remaining in remission is greatest in patients who express both CD80 and CD86 [4]. AML cells can shed ligands for co‐stimulatory molecules such as the 4‐1BB ligand, which may allow the leukaemia to block T cell attack by the binding of soluble ligand to the T cell [33]. The class II‐associated invariant chain self‐peptide (CLIP) is expressed variably in AML.…”
Section: Interaction Of the Immune System With Amlmentioning
confidence: 99%
“…6,7 Moreover, we and others have already shown that regulatory soluble factors produced by host T cells or DC contribute to the regulation and mediation of antileukemic T-cell function. 3 Moreover, cellular factors such as regulatory T cells (T reg ) consisting of naturally occurring T reg and several subgroups of extrathymically activation-induced T reg are known to regulate immune responses. T reg are classically divided into naturally occurring CD4 + CD25 + FOXP3 + T reg ( n T reg ) and activation-induced T reg ( i T reg ) appearing after peripheral antigen stimulation.…”
mentioning
confidence: 99%